Implementasi Augmented Reality sebagai Media Pengenalan Alat Musik Tradisional Bali dengan Metode FAST Corner Detection Berbasis Android (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
There are so many traditional Balinese musical instruments that some people don't know about. With technological advances, the introduction of traditional musical instruments can use the Augmented Reality (AR) method. The researcher used ceng-ceng, genggong, gong, gangsa, and rindik 3D objects as 3D models. The algorithm used is FAST Corner Detection to determine the key points on the marker so that it becomes a reference for detecting 3D objects of Balinese musical instruments. Application testing is carried out by blackbox testing and application performance testing which includes testing of scanning markers that are positioned perpendicular to the camera, rotated 90°, 180°, and 270°. In addition, the application response time to markers was tested using three smartphones of different types and specifications. The three devices include Mi 10T, Realme 3 Pro, and Realme C11. The blackbox test results obtained good results. The results of the marker scanning test, namely the angle of rotation of the marker does not affect object detection. As for the response time test, it was found that the Mi 10T has the fastest average response time of 1.35 seconds, then the Realme 3 Pro with an average response time of 1.49 seconds, and the Realme C11 with an average response time of 1.82 seconds.